School in Alto Adige after World War I: between Italian occupation and Tyrolean resistance (1918-1922). - Dessardo, Andrea (Rivista di Storia dell’Educazione, 2017)
Two minorities, one inside the other, tried to resist to the regime change in Alto Adige in the first afterwar, from the downfall of Austria-Hungary until the arising of Fascism: Germans, minority in the Kingdom of Italy, but firm majority from Salorno to the Brenner Pass; and Italians, that despite the new authorities' efforts, felt more linked to Innsbruck than to Trento. The essay surveys the Tyrolian society mood through the records of an inspection driven in February 1920 in the region girls' schools and it analyses also the failure of the Corbino's Act in August 1921, with which Luigi Credaro, the general civilian commissioner, wanted to preserve Italians from the Germanisation.